Effect of exercise training on cardiac function and glucose metabolism in the ischemic border zone: insights from multi-modal imaging techniques - Jun Zhang; Jun Zhang; Jun Zhang; Chunrong Jin; Xiao Han; Xiao Han; Ping Wu; Ping Wu; Jianbo Cao; Jianbo Cao; Jianbo Cao; Sheng He; et al. (Frontiers in Cardiovascular Medicine)
AimsThis study aimed to evaluate the impact of early exercise following acute myocardial infarction (AMI) on cardiac function, myocardial remodeling, glucose metabolism, and its molecular changes using cardiac magnetic resonance (CMR) imaging and positron emission tomography (PET).Methods and resultsThirteen rats (MI-exercise, MIE) underwent an 8-week treadmill exercise training initiated 1 week after AMI. Longitudinal assessments were conducted using 7T CMR and 18F-FDG PET/CT imaging at baseline, 4 weeks and 8 weeks following the commencement of exercise. Molecular and pathological analyses, including qPCR and Western blot, were conducted to evaluate mRNA and protein expression related to glucose metabolism. Exercise training led to significant improvements in stroke volume (SV), left ventricular ejection fraction (LVEF), and fraction wall thickening (WT%) from 4 weeks onward, as assessed by CMR, which strongly correlated with increased myocardial glucose uptake, as measured by 18F-FDG PET (P < 0.05). Histological analysis revealed a marked reduction in inflammatory cell infiltration and fibrosis percentage (MIE vs. MIC: 23.42 ± 5.4% vs. 40.63 ± 8.9%, P < 0.05), accompanied by an increase in myocardial cross-sectional area (MIE vs. MIC: 817.15 ± 36.54 μm2 vs. 379.28 ± 67.99 μm2, P = 0.002). RNA sequencing demonstrated upregulation of pathways associated with cellular metabolism. Additionally, the expression levels of GLUT4 and PFKFB3 mRNA and proteins were significantly elevated following exercise training.ConclusionsEarly exercise post-AMI, as assessed by CMR and PET imaging, significantly improved cardiac function, reduced myocardial remodeling, and enhanced glucose metabolism. These benefits were mediated through the upregulation of GLUT4 and PFKFB3 expression, underscoring the potential of exercise as a therapeutic strategy in post-AMI management.